Penentuan Pola Frekuensi Menggunakan Algoritma Apriori pada Sistem Informasi Berbasis Web - Herlawati , Herlawati; Handayanto , Rahmadya Trias; Rejeki , Sri; Priatna , Wowon; Atika , Prima Dina; Rofiah , Syahbaniar; Retnoningsih , Endang; Saputra , Faisal Adi; Pradana , Galih Apriansha (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Currently, technology can affect services in any field, both in areas such as salon services and sales of clothing products. How to plan a marketing strategy using the web based on service transaction data and products that are most often chosen by customers. Therefore, an information system for determining frequency patterns is needed using the website-based Apriori Algorithm method. The results of research on salons based on the type of beauty treatment obtained for the type of treatment with a minimum confidence = 70%, the first confidence value is 63% if the customer chooses to wash (shampoo), the customer chooses scissors, the second the confidence value is 100%, if the customer chooses to blow then chooses also cut, and the third confidence value is 86% if the customer chooses creambath then the customer chooses to cut too. Meanwhile at the shop clothes determining the frequency pattern of types of clothes with a minimum value of confidence = 70% so that the results include if a customer buys a veil, the customer buys a robe with a confidence value of 71.43% and if a customer buys khimar then the customer will also buy a robe with a confidence value of 78, 57%. With these results salon and clothing store owners can determine marketing strategies by providing the right product and service recommendations to customers.